Manajemen Resiko dalam Perpajakan - Arna Suryani (Universitas Batanghari, 2021)
This research aims to identify and analyze how risk management is and what tax risks can arise, so it is necessary to carry out risk management in taxation. The research method used is literature review research method by examining the concepts and theories used based on the available literature, especially articles published in various scientific journals. Good risk management will minimize the losses faced by the company, so that the company can maintain its survival and can even develop into a large and successful company in its business. Tax risk management is important for every company, so that each company can manage tax risk properly and can reduce the negative impact of risks experienced by the company. In fulfilling tax obligations, companies need to deduct or collect, deposit and report all of which must comply with applicable tax regulations. Successful tax risk management can only be achieved by companies with a strong tax risk control framework, both internally and externally.